Isotope evidence for multiple sources of B and Cl in Middle Miocene (Badenian) evaporites, Carpathian Mountains. (January 2021) - Zhao, Yao; Wei, Hai-Zhen; Liu, Xi; Wang, Yi-Jing; Jiang, Shao-Yong; Eastoe, Christopher J.; Peryt, Tadeusz M.
Abstract: Evaporites of Middle Miocene Badenian stage occur widely in basins from the Carpathian Mountain region (Poland, Slovakia and Ukraine), but their source and formation process are still debatable. A detailed boron isotope study in combination with previous chlorine isotope and chemistry data of the salt samples from three localities (Wieliczka mine, Trans-Carpathian Basin, East Slovakian Basin) reveal ranges of δ 11 B (−4.5 to +35.7‰) and δ 37 Cl (−0.2 to +0.8‰). Modelling calculation indicates that both Rayleigh fractionation and incorporation of fluid inclusion solutes cannot cause such a large shift on δ 11 B values in halite. Instead, the B and Cl isotope data imply multiple brine sources, including evaporite brine, dissolved diapiric halite and basin brine in addition to the predominant seawater source during the formation of these evaporites. At Wieliczka salt mine, a positive δ 11 B excursion (from −5‰ to + 30‰) matches the negative δ 37 Cl variation (from +0.5 ± 0.1‰ to -0.2‰) stratigraphically upwards, which indicate both terrestrial boron and non-marine chloride made significant contributions to the composition of the basin brine during the early development of the basin. In the upper column, the δ 11 B values are within the marine range, but show influence by the sorption of boron onto clay, whereas the δ 37 Cl values at +0.5‰ still indicate the presence of non-marine chloride, possibly from recrystallized, diapiric halite. In the Trans-Carpathian Basin, constant δ 37 Cl (+0.3‰) and δ 11 B (+15‰) in the middle of the profile are consistent with a dominant marine source, whereas the lower δ 11 B (+2.2‰) and higher δ 37 Cl (+0.8‰) in the lower column suggest terrestrial fresh water flowed into the basin during the formation of basal halite. Halites in the upper part of the profile show near 0‰ of δ 37 Cl, suggesting incorporation of Cl from a mixture of expelled basin brines. In the Slovakian Basin, the δ 11 B values (+18.1 to +19.1‰) at the base of the profile lie within the marine range, but high δ 37 Cl values (+0.7 to +0.8‰) require a non-marine chloride source. In the upper part of the profile, boron isotope data indicate a change from marine (+12.2 to +23.4‰) to non-marine (+5.4 to +6.1‰) derivation of B, but the sources of Cl remain marine (+0.0 to +0.5‰). Overall, both B and Cl isotopes show coupled variation in the Middle Miocene Badenian evaporites and suggest multiple sources of B and Cl. Highlights: Research Highlights: Chlorine and boron isotopes in the Badenian evaporites were investigated systematically. Kinetic isotope fractionation and boron from fluid inclusions induce minor shifts in δ 11 B in halite. Multiple sources from seawater, terrestrial water and buried brines to the evaporites were defined. Evolution processes along the stratum of three evaporite basins were well constrained.